TRADITIONAL LIFE OF BAYUNG GEDE COMMUNITY AND ITS DEVELOPMENT AS CULTURAL ATTRACTION - I Nengah Suastika; Gede Putu Agus Jana Susila; Ni Made Ary Widiastini (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The village of Bayung Gede is one of the Bali Aga villages that still firmly maintain the traditions and values of traditional Balinese life. This pattern of traditional life appears in religious ritual, social and agricultural activities carried out by the community. Ritual activities in the village can be seen in the ceremony of menek bayan1) , a wedding ceremony which uses cows as payment, the ceremony of ari-ari2) in which the placenta is hung, ngaben or cremation ceremony and the traditional ceremony in the temple. Social activities conducted by the community can be seen in the activities of joy (marriage, teeth filing, three month ceremonies), and grief (death, sickness, and cremation), mutual cooperation in the temple and cleaning the tools, the use of organic fertilizers, the use of plants for consumption. These cultural activities can be utilized and presented as cultural tourism attractions, thereby generating economic benefits for the local community.